57‐3: MircoLED Display Integration on 300mm Advanced CMOS Platform. Issue 1 (28th June 2022) - Steudel, Soeren; Vertommen, Johan; Le Boulbar, Emmanuel; Buscemi, Giuseppe; Bach, Lars; Van Huylenbroeck, Stefaan; Arumugam, Hariharan; La Tulipe, Douglas Charles; De Vos, Joeri; Miller, Andy; Osman, Haris; Rebibis, Kenneth June
Abstract : We show for the first time a microLED display integration flow in a 300mm CMOS manufacturing platform resulting a pixel density of 9150dpi with a 3μm pixel pitch and a brightness for blue μLED in excess of 600kcd/m 2 @100A/cm 2 .